Outside Earnings, Absence, and Activity: Evidence from Germany Parliamentarians - Felix Arnold; Björn Kauder; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine moonlighting by politicians in Germany. In July 2007, the German Supreme Court adjudicated that members of parliament (MPs) have to publish details of their outside earnings. Using panel data models, we investigate how outside earnings are correlated with absence and parliamentary activity. The results do not indicate that outside earnings are correlated with absence rates and speeches; but they do suggest that outside earnings are somewhat negatively correlated with oral contributions, interpellations, and group initiatives. We propose that the results for Germany do not corroborate evidence on other countries such as Italy because party discipline, institutions, and political cultures differ across countries.
Keywords: D72; H11; 330; moonlighting by politicians; outside earnings; attendance and activity in parliament; good and bad politicians